Self-powered photoelectric detector based on Cs2CuBiI6 film and preparation method thereof
By using Cs2CuBiI6 film material and specific preparation methods, the instability and lead toxicity of existing perovskite-based photodetector materials are solved, and the high efficiency, environmental protection and low-cost characteristics of self-powered photodetectors are achieved.
Patent Information
- Application Number
- CN202411671510.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing perovskite-based photodetectors have limited their application due to material instability and lead toxicity, and have complex processes, high costs and high energy consumption.
A self-powered photodetector is formed by a specific preparation method using a Cs2CuBiI6 film as the material of the photodetector, including a substrate, a PEDOT:PSS conductive polymer layer, a Cs2CuBiI6 film layer, a PC61BM film layer, a BCP layer and a silver electrode.
The environmental friendliness and stability of the material is achieved, the toxicity of the device is reduced, the photoelectric detection performance is improved, the switching ratio and responsiveness is increased, the process is simplified, and the cost is reduced.
Smart Images

Figure CN119677286A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor photoelectric detection technology, and specifically relates to a self-powered photoelectric detector based on Cs2CuBiI6 film and a preparation method thereof. Background Art
[0002] In recent years, lead halide perovskites are becoming popular semiconductors in the field of optoelectronics due to their excellent optoelectronic properties, namely high photoluminescence quantum yield, narrow emission peak, tunable band gap, efficient charge generation and broadband absorption. Despite the booming development of lead halide perovskites, the presence of toxic lead has hindered their further development, prompting researchers to explore lead sequestration technology (to prevent lead leakage) or develop new environmentally friendly lead-free perovskites. Among these lead-free perovskites, bismuth (Bi)-based perovskite materials have been widely used due to their excellent environmental stability, high absorption coefficient (~105cm -1 ) and an ionic radius similar to that of Pb, it is a promising candidate material to replace toxic Pb-based perovskites.
[0003] Cs2ABiX6 is a double perovskite structure material. By replacing the Pb metal cation with two different elements at the same time, a double perovskite material composed of different octahedral structures arranged alternately is synthesized. Compared with traditional ABX3-type perovskite materials, CsABiX6 has higher structural stability and environmental friendliness. In addition, they have a relatively narrow band gap width (about 2.0 electron volts) and good light absorption performance, and have good application prospects in new photodetectors (CCWu, QHZhang, Y.Liu, W.Luo, X.Guo, Z.Huang, H.Ting, WH Sun, XRZhong, SYWei, SFWang, ZJChen, and LXXiao, Adv.Sci.1700759 (2017); ETMcClure, MRBall, W.Windl, and PM Woodward, Chem.Mater.28,1348 (2016)). At present, all reported perovskite-based photodetectors are based on CH3NH3PbX3 and CsPbX3 material systems. The instability of the material itself and lead toxicity are the main bottlenecks limiting the practical application of this type of device.
[0004] Therefore, it is necessary to conduct in-depth research on perovskite materials. On the basis of optimizing the preparation process, it is possible to achieve higher quality imaging when the materials are used in self-powered photodetectors and reduce harm to the human body. Summary of the invention
[0005] In view of the problems of the prior art, the present invention aims to solve the problems of complex process, high cost, high energy consumption, etc. in the prior art, and to invent a self-powered photodetector based on Cs2CuBiI6 thin film and a preparation method thereof. The method is simple to operate and the prepared photodetector has excellent photoelectric detection performance.
[0006] In order to achieve the above-mentioned invention object, the specific technical solution of the present invention is:
[0007] 1. A self-powered photodetector based on Cs2CuBiI6 thin film, comprising a substrate, on which a PEDOT:PSS conductive polymer layer, a Cs2CuBiI6 thin film layer, a PC 61 BM thin film layer, BCP layer and silver electrode.
[0008] Preferably, the substrate is ITO glass with a thickness of 1.0-1.1 mm.
[0009] Preferably, the thickness of the PEDOT:PSS conductive polymer layer is 160-180nm, the thickness of the Cs2CuBiI6 thin film layer is 90-110nm, and the thickness of the PC 61 The thickness of the BM film layer is 90-110nm, and the thickness of the BCP layer is 60-80nm.
[0010] The self-powered photodetector based on Cs2CuBiI6 thin film, wherein the preparation method of Cs2CuBiI6 is:
[0011] (1) CsI, CuI, BiI3, hydroiodic acid and hypophosphorous acid are mixed according to the ratio and heat treated at 80° C. until they are completely dissolved;
[0012] (2) gradually raising the temperature of the completely dissolved solution to 180-190°C within 4 hours, keeping the temperature for 2-4 hours, then cooling the solution to room temperature within 4 hours, then raising the temperature of the solution to 180-190°C within 4 hours, keeping the temperature for 2-4 hours, cooling the solution from 180°C to 100°C within 72 hours, then cooling the solution from 100°C to 20°C within 72 hours, keeping the temperature at 20°C for 4-6 hours, filtering out the synthesized solid material and washing it with acetone to obtain Cs2CuBiI6 powder.
[0013] Further preferably, the preparation method of Cs2CuBiI6 is:
[0014] (1) 519.62 mg CsI, 190.45 mg CuI and 589.69 mg BiI3 were dissolved in 10 ml hydroiodic acid (HI) and 2 ml hypophosphorous acid, and then heat treated at 80°C until completely dissolved;
[0015] (2) The completely dissolved solution was gradually heated to 180°C within 4 hours, kept warm for 2 hours, then cooled to room temperature within 4 hours, heated to 180°C within 4 hours, kept warm for 2 hours, cooled from 180°C to 100°C within 72 hours, cooled from 100°C to 20°C within 72 hours, kept warm at 20°C for 5 hours, filtered out the synthesized solid material and washed with acetone to obtain Cs2CuBiI6 powder.
[0016] 2. A method for preparing a self-powered photodetector based on Cs2CuBiI6 thin film, comprising the following steps:
[0017] (1) dissolving Cs2CuBiI6 powder in dimethyl sulfoxide, and subjecting it to heat treatment to dissolve and form a Cs2CuBiI6 precursor solution for later use;
[0018] (2) Connect the PC 61 Dissolve BM in chlorobenzene, stir and dissolve for later use;
[0019] (3) Dissolve BCP in isopropanol and heat-treat it to dissolve it for later use;
[0020] (4) Using ITO glass as a substrate, cleaning and plasma treatment were performed to form a hydrophilic surface, a PEDOT:PSS solution was coated on the upper surface of the ITO substrate, and then annealed at 100°C for 10 min under nitrogen conditions, and cooled to form a PEDOT:PSS conductive polymer layer, and then a Cs2CuBiI6 precursor solution was coated on the surface of the PEDOT:PSS conductive polymer layer, and annealed at 100°C for 10 min under nitrogen conditions, and cooled to form a Cs2CuBiI6 thin film layer, and then PC 61 BM solution and BCP solution were coated and annealed at 100 °C for 10 min under nitrogen to form PC 61 BM film layer, BCP layer;
[0021] (5) The obtained device is transferred into a vacuum chamber and coated with silver electrodes.
[0022] Further preferably, the method for preparing the self-powered photodetector based on Cs2CuBiI6 thin film comprises the following steps:
[0023] (1) Dissolve 1 mmol of Cs2CuBiI6 powder in 1 mL of dimethyl sulfoxide (DMSO), heat and stir at 60°C for 20 min, cool to room temperature, and filter with a 0.45 μm filter for later use;
[0024] (2) 20 mg PC 61 Dissolve BM in 1 mL of chlorobenzene, stir until the solid is completely dissolved, filter with a 0.22 μm filter head and store in another clean small brown bottle for later use;
[0025] (3) Dissolve 7 mg of BCP in 10 mL of isopropanol and heat and stir at 40 °C for at least 24 h until the solid is completely dissolved to form a BCP solution for use;
[0026] (4) Using ITO glass as a substrate, it was cleaned with deionized water, and then ultrasonically treated with anhydrous ethanol and acetone for 20 minutes each. The surface liquid was blown off with nitrogen and dried in an oven. Finally, the substrate was treated with oxygen plasma for 300 seconds to form a hydrophilic surface. The PEDOT:PSS solution was sucked with a syringe and dropped on the ITO substrate with a 0.22 μm filter. The solution was spin-coated at 1000 rpm for 9 seconds and 3000 rpm for 30 seconds. The solution was then annealed at 100 °C for 10 minutes under nitrogen conditions and cooled to room temperature to form a PEDOT:PSS conductive polymer layer. The Cs2CuBiI6 precursor solution was then spin-coated at 800 rpm for 9 seconds and 1500 rpm for 30 seconds. The solution was then annealed at 100 °C for 10 minutes under nitrogen conditions to form a Cs2CuBiI6 thin film layer after cooling. The PC 61 The BM precursor solution and the BCP precursor solution were spun at 1000 rpm for 9 s and 3500 rpm for 30 s and annealed at 100 °C for 10 min under nitrogen to form PC 61 BM film layer, BCP layer;
[0027] (5) The obtained device was transferred into a vacuum chamber and the vacuum degree was 5×10 -4 A silver electrode with a thickness of 150 nm was deposited in an environment of 100 Pa.
[0028] The beneficial effects of the present invention are as follows: the Cs2CuBiI6 synthesized by the technical solution disclosed in the present invention has a wide absorption spectrum and is inorganic and lead-free, greatly reducing the toxicity of the device and increasing the stability of the device, and using BCP as an electron blocking layer reduces the dark current of the device, thereby increasing the switching ratio and responsiveness of the self-powered photodetection device. The method of the present invention is easy to operate and control, and the prepared product has excellent performance.
[0029] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0031] Figure 1This is a scanning electron microscope photo of Cs2CuBiI6 thin film;
[0032] Figure 2 is the UV-visible absorption spectrum of Cs2CuBiI6 thin film;
[0033] Figure 3 is the device structure of photodetectors (PDs);
[0034] Figure 4 The IV curves of PDs under different wavelengths of light;
[0035] Figure 5 The IT curves of PDs under 0V bias and different light intensities;
[0036] Figure 6 is the rise and fall response time of PDs under 0V bias;
[0037] Figure 7 It is the detection diagram of the responsivity and specific detectivity of PDs;
[0038] Figure 8 To test the stability of PDs in cycles;
[0039] Fig. 9 This is a graph showing the stability of PDs in air. DETAILED DESCRIPTION
[0040] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0041] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0042] Before preparing the self-powered photodetector, the bismuth-based inorganic metal halide material Cs2CuBiI6 is prepared as follows:
[0043] (1) Dissolve 519.62 mg CsI, 190.45 mg CuI and 589.69 mg BiI3 in 10 ml hydroiodic acid and 2 ml hypophosphorous acid in a beaker, then place the beaker on a hot plate and stir and heat at 80°C until completely dissolved.
[0044] (2) The solution is then transferred to an absolutely clean liner. In an oven, the completely dissolved solution is gradually heated to 180°C within 4 hours and kept warm for 2 hours. The solution is then cooled to room temperature within 4 hours. The solution is then heated to 180°C within 4 hours and kept warm for 2 hours. The solution is then cooled from 180°C to 100°C within 72 hours. The solution is then cooled from 100°C to 20°C within 72 hours. The solution is kept warm at 20°C for 5 hours. The synthesized solid material is filtered out and washed with acetone to obtain Cs2CuBiI6 powder.
[0045] Example 1
[0046] A self-powered photodetector based on Cs2CuBiI6 is prepared as follows:
[0047] (1) Dissolve 1 mmol of Cs2CuBiI6 powder in 1 mL of dimethyl sulfoxide, heat and stir at 60°C for 20 min, cool to room temperature, and filter with a 0.45 μm filter for later use.
[0048] (2) 20 mg PC 61 BM was dissolved in 1 mL of chlorobenzene and stirred until the solid was completely dissolved. After filtering with a 0.22 μm filter head, it was stored in another clean small brown bottle for later use.
[0049] (3) Dissolve 7 mg of BCP in 10 mL of isopropanol and heat and stir at 40 °C for at least 24 h until the solid is completely dissolved to form a BCP solution for use;
[0050] (4) With a thickness of 1 mm and an area of 4 cm 2 The ITO glass was used as the substrate, cleaned with deionized water, and then ultrasonically treated with anhydrous ethanol and acetone for 20 minutes each, and then the surface liquid was blown off with nitrogen and dried in an oven. Finally, the substrate was treated with oxygen plasma for 300 seconds to form a hydrophilic surface, and the PEDOT:PSS solution was sucked with a syringe and dropped on the ITO substrate with a 0.22μm filter head. It was spin-coated at 1000rpm for 9s and 3000rpm for 30s, and then annealed at 100℃ for 10min under nitrogen conditions and cooled to room temperature to form a PEDOT:PSS conductive polymer layer. Similarly, the Cs2CuBiI6 precursor solution was rotated at 800rpm for 9s and 1500rpm for 30s, and annealed at 100℃ for 10min under nitrogen conditions to form a Cs2CuBiI6 thin film layer after cooling, and then the PC 61The BM precursor solution and the BCP precursor solution were spun at 1000 rpm for 9 s and 3500 rpm for 30 s and annealed at 100 °C for 10 min under nitrogen to form PC 61 BM film layer, BCP layer;
[0051] (5) The device obtained in step 5 was transferred into a vacuum chamber and the vacuum degree was 5×10 -4 A silver (Ag) electrode with a thickness of 150 nm was deposited in an environment of 100 Pa. Figure 3 Device structure diagram of photodetectors (PDs) shown.
[0052] After testing, in this embodiment, the thickness of the PEDOT:PSS conductive polymer layer is 160nm, the thickness of the Cs2CuBiI6 thin film layer is 90nm, the thickness of the PC61BM thin film layer is 91nm, and the thickness of the BCP layer is 65nm.
[0053] In the manufacturing process of this embodiment, the obtained Cs2CuBiI6 thin film layer was tested and the following results were obtained: Figure 1 Scanning electron micrographs shown, and Figure 2 UV-visible absorption spectrum of Figure 1 It can be shown that the film has a dense morphology. Figure 2 This indicates that the film has a broad absorption spectrum.
[0054] The prepared photodetectors (PDs) were tested for performance and obtained Figure 4 The IV curves of the PDs shown under different wavelengths of light; Figure 5 The IT curves of PDs under different light intensities under 0V bias are shown; Figure 6 The rise and fall response time of PDs under 0V bias is shown; Figure 7 Responsivity and specific detectivity of the PDs shown; Figure 8 Stability detection diagram of the cycle tested PDs shown; Fig. 9 This is a graph showing the stability of PDs in air.
[0055] Depend on Figure 4-Figure 9 It can be explained that the device has a self-powered function by forming a built-in electric field in the space charge region of the internal components of the device. At the same time, the device also shows an excellent switching ratio, fast response speed and good stability. The above tests can reflect that the photoelectric detection device prepared in this embodiment has a fast impact.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A self-powered photodetector based on Cs2CuBiI6 thin film, comprising a substrate, characterized in that: The substrate is provided with a PEDOT:PSS conductive polymer layer, a Cs2CuBiI6 thin film layer, a PC 61 BM thin film layer, BCP layer and silver electrode.
2. A self-powered photodetector based on Cs2CuBiI6 thin film according to claim 1, characterized in that: The substrate is ITO glass with a thickness of 1.0-1.1 mm.
3. A self-powered photodetector based on Cs2CuBiI6 thin film according to claim 1, characterized in that: The thickness of PEDOT:PSS conductive polymer layer is 160-180nm, the thickness of Cs2CuBiI6 thin film layer is 90-110nm, and the thickness of PC 61 The thickness of the BM film layer is 90-110nm, and the thickness of the BCP layer is 60-80nm.
4. A self-powered photodetector based on Cs2CuBiI6 thin film according to claim 1, characterized in that: The preparation method of Cs2CuBiI6 is: (1) CsI, CuI, BiI3, hydroiodic acid and hypophosphorous acid are mixed according to the ratio and heat treated at 80° C. until they are completely dissolved; (2) gradually raising the temperature of the completely dissolved solution to 180-190°C within 4 hours, keeping the temperature for 2-4 hours, then cooling the solution to room temperature within 4 hours, then raising the temperature of the solution to 180-190°C within 4 hours, keeping the temperature for 2-4 hours, cooling the solution from 180°C to 100°C within 72 hours, then cooling the solution from 100°C to 20°C within 72 hours, keeping the temperature at 20°C for 4-6 hours, filtering out the synthesized solid material and washing it with acetone to obtain Cs2CuBiI6 powder.
5. A self-powered photodetector based on Cs2CuBiI6 thin film according to claim 4, characterized in that: The preparation method of Cs2CuBiI6 is: (1) 519.62 mg CsI, 190.45 mg CuI and 589.69 mg BiI3 were dissolved in 10 ml hydroiodic acid and 2 ml hypophosphorous acid, and heat treated at 80°C until completely dissolved; (2) The completely dissolved solution was gradually heated to 180°C within 4 hours, kept warm for 2 hours, then cooled to room temperature within 4 hours, heated to 180°C within 4 hours, kept warm for 2 hours, cooled from 180°C to 100°C within 72 hours, cooled from 100°C to 20°C within 72 hours, kept warm at 20°C for 5 hours, filtered out the synthesized solid material and washed with acetone to obtain Cs2CuBiI6 powder.
6. A method for preparing a self-powered photodetector based on Cs2CuBiI6 thin film, characterized in that: The steps include: (1) dissolving Cs2CuBiI6 powder in dimethyl sulfoxide, and subjecting it to heat treatment to dissolve and form a Cs2CuBiI6 precursor solution for later use; (2) Connect the PC 61 Dissolve BM in chlorobenzene, stir and dissolve for later use; (3) Dissolve BCP in isopropanol and heat-treat it to dissolve it for later use; (4) Using ITO glass as a substrate, cleaning and plasma treatment were performed to form a hydrophilic surface, a PEDOT:PSS solution was coated on the upper surface of the ITO substrate, and then annealed at 100°C for 10 min under nitrogen conditions, and cooled to form a PEDOT:PSS conductive polymer layer, and then a Cs2CuBiI6 precursor solution was coated on the surface of the PEDOT:PSS conductive polymer layer, and annealed at 100°C for 10 min under nitrogen conditions, and cooled to form a Cs2CuBiI6 thin film layer, and then PC 61 BM solution and BCP solution were coated and annealed at 100 °C for 10 min under nitrogen to form PC 61 BM film layer, BCP layer; (5) The obtained device is transferred into a vacuum chamber and coated with silver electrodes.
7. The method for preparing a self-powered photodetector based on Cs2CuBiI6 thin film according to claim 6, characterized in that: The steps include: (1) Dissolve 1 mmol of Cs2CuBiI6 powder in 1 mL of dimethyl sulfoxide (DMSO), heat and stir at 60°C for 20 min, cool to room temperature, and filter with a 0.45 μm filter for later use; (2) 20 mg PC 61 Dissolve BM in 1 mL of chlorobenzene, stir until the solid is completely dissolved, filter with a 0.22 μm filter head and store in another clean small brown bottle for later use; (3) Dissolve 7 mg of BCP in 10 mL of isopropanol and heat and stir at 40 °C for at least 24 h until the solid is completely dissolved to form a BCP solution for use; (4) ITO glass was used as a substrate and cleaned with deionized water. It was then ultrasonically treated with anhydrous ethanol and acetone for 20 min each. The surface liquid was blown off with nitrogen and dried in an oven. Finally, the substrate was treated with oxygen plasma for 300 s to form a hydrophilic surface. The PEDOT:PSS solution was drawn with a syringe and dropped on the ITO substrate with a 0.22 μm filter. The solution was spin-coated at 1000 rpm for 9 s and 3000 rpm for 30 s. The solution was then annealed at 100 °C for 10 min under nitrogen conditions and cooled to room temperature to form a PEDOT:PSS conductive polymer layer. The Cs2CuBiI6 precursor solution was then spin-coated at 800 rpm for 9 s and 1500 rpm for 30 s. The solution was then annealed at 100 °C for 10 min under nitrogen conditions to form a Cs2CuBiI6 thin film layer after cooling. The PC 61 The BM precursor solution and the BCP precursor solution were spun at 1000 rpm for 9 s and 3500 rpm for 30 s and annealed at 100 °C for 10 min under nitrogen to form PC 61 BM film layer, BCP layer; (5) The obtained device was transferred into a vacuum chamber and the vacuum degree was 5×10 -4 A silver electrode with a thickness of 150 nm was deposited in an environment of Pa.
Citation Information
Patent Citations
Method for synthesizing iodine-bismuth-copper film through room-temperature in-situ control and photoelectric conversion device assembled by iodine-bismuth-copper film
CN110660915A
Self-driven difunctional photoelectric detector and preparation method thereof
CN115172592A
Preparation method of self-powered CsCu2I3 film ultraviolet photoelectric detector
CN115732583A
Naphthylamine-based quasi-two-dimensional perovskite photoelectric detector and preparation method thereof
CN115915872A
Self-powered ghz solution-processed hybrid perovskite photodetectors
US20180075977A1